(untitled) (Journal of Asian Development Studies, 2020)
Brain drain is the crucial point of all societies due to astonishing outflow of competent and skilled hands. Flourishing Nations always focus on human growth and development but the dilemma of developing countries is the migration of advanced and highly skilled individuals like scientist, doctors and IT professionals to developed countries with an increasing trend. Pakistan is also victim of this painful and hurting phenomenon. Many discussions present the effects of Brain Drain on economy of Pakistan. We have reconsidered some empirical studies showing clues of brain drain in Pakistan. This research article examines empirical influences of remittances, political instability and unemployment on brain drain phenomenon in Pakistan by employing Johanson co-integration technique. Annual time series data is used over the time period of 1980-2013. Our empirical results show that all independent variables have positive and long run relationship with brain drain phenomenon.